Strategi Pengelolaan Sdm Guna Peningkatan Kinerja Karyawan Di Era Digital (Studi Kasus Pada Franchise Mixue Teluk Jambe, Karawang) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2025)
Study examines Mixue digital HR strategy addressing digital era challenges and youth workforce needs. Analyzes digital implementation in recruitment, training, and performance evaluation at Mixue Teluk Jambe. Assesses HRIS, digital training effectiveness, productivity impacts, and youth-oriented technology integration challenges.This qualitative case study research examines Mixue Teluk Jambe digital HR strategy through interviews and field observations in May 2025. The location was chosen as a representation of the challenges of local F&B retail digitalization. Data is presented descriptively to clearly describe HR management practices, employee perceptions, and technology implementation in the field. Mixue Teluk Jambe optimizes HR management through three digital approaches: technology training for daily operations, integrated HRIS system, and communication via WhatsApp (internal) and Instagram (external). This implementation has successfully increased operational efficiency, strengthened team collaboration, and attracted young talent through adaptive digital strategies. Mixue Teluk Jambe enhances business performance through digital HR transformation featuring: tech training, HRIS recruitment system, and WhatsApp/Instagram communication. Future development requires: integrated apps, microlearning training, and TikTok/LinkedIn expansion. This strategy strengthens competitiveness while serving as a digital HR model for F&B businesses.